(3GdLhGgQ GdeVjI aj WHbGJ GdMfajIs - (3CHh eMeO eMjj GdOjf YHO GdbGOQ Hf eMeO Hf fUQ Gddg GdeYQha HGHf CHi GdhaGA GdbQTi GdJejei GdeUQjs; (3CHh YHO Gddg (B((3CHj YjSi(B) (3eMeO GdegOj Hf CMeO Hf Ydj Hf CHj GdeMGSf jhSa GdaGSj,J (B1109 (3g` s ((3HdOI QhOS s)
(3ChdgG (B:s
(3JJab ai ChdgG eY GdfSNI GdChdi , HGNJdGa ai HYV GdCdaGX s
(3BNQgG (B:s
(3JJab ai BNQgG eY GdfSNI GdChdi , HGNJdGa ai HYV GdCdaGX s
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe GdEeGe hGdNWjH YHO GdcQje Hf TgGH GdOjf CMeO GdMeUi GdMdHi GdMfais
(3HChdgG Jedc dbGVi HhdGjI CSjhW SfI (B1131(3g`s
(3edJbW efg s
(3fSNI KGfjI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs